Bodies and disciplines : intersections of literature and history in fifteenth-century England - Hanawalt, Barbara A., 1941-; Wallace, David, 1954- (Medieval cultures, 1996)
Centered on practices of the body-human bodies, the "body politic"--Bodies and Disciplines considers a fascinating and largely uncanonical group of texts, as well as public dramas, rituals, and spectacles, from multidisciplinary perspectives. The result is a volume that incorporates insights from history, literature, medieval studies, and critical theory, drawing from the strengths of each discipline to illuminate a relatively little-studied period